Long-term prevention of catheter-associated urinary tract infections among critically ill patients through the implementation of an educational program and a daily checklist for maintenance of indwelling urinary catheters: A quasi-experimental study. Issue 8 (February 2019) - Menegueti, Mayra Gonçalves; Ciol, Marcia A.; Bellissimo-Rodrigues, Fernando; Auxiliadora-Martins, Maria; Gaspar, Gilberto Gambero; Canini, Silvia Rita Marin da Silva; Basile-Filho, Anibal; Laus, Ana Maria
Abstract: Background: Removing an indwelling urinary catheter as soon as possible is the cornerstone of catheter-associated urinary tract infections (CAUTI) prevention. However, implementing this measure may be challenging in clinical settings. To evaluate the impact of implementing a healthcare workers (HCWs) educational program and a daily checklist for indwelling urinary catheter indications among critical patients on the incidence of CAUTI. Methods: This was a quasi-experimental study performed in a general intensive care unit of a tertiary-care hospital over a 12 years period, from January 1, 2005 to December 31, 2016. Rates of urinary catheter use and incidence density of CAUTI were monthly evaluated following the Centers for Disease Control and Prevention (CDC) criteria throughout the study period. Phase I (2005–2006) was the pre-intervention period. In phase II (2007–2010), HCWs routine training on CAUTI prevention was performed twice-a-year. In phase III (2011–2014), we implemented a daily checklist for indwelling urinary catheter indications, in addition to the biannual training. In phase IV, (2015–2016) the biannual training was replaced by training only newly hired HCWs and the daily checklist was maintained. Results: The mean rate of urinary catheter utilization decreased from phase I to phase IV (73.1%, 74.1%, 54.9%, and 45.6%, respectively). Similarly, the incidence density of CAUTI decreased from phase I to phase IV (14.9, 7.3, 3.8, and 1.1 per 1000 catheter-days, respectively). Conclusions: HCWs education and daily evaluation of indwelling urinary catheter indications were highly effective in reducing the rates of catheter utilization as well as the incidence density of CAUTI.